Sailors Club, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
The postcard shows a sailor, a young man and a civilian (with his back to the camera) standing outside the Sailors and Soldiers' Club in Port of Spain, Trinidad. In this close up view, we can see that this is a wooden building.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Sailors--Trinidad and Tobago; Boys--Trinidad and Tobago; Bars (Drinking establishments)--Trinidad and Tobago; Buildings--Trinidad and Tobago; [1924]; Windows--Trinidad and Tobago; Wooden windows--Trinidad and Tobago; Clubs--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Architecture--Trinidad and Tobago; Soldiers--Trinidad and Tobago; Architecture--Details; Tents--Trinidad and Tobago; Hats--Trinidad and Tobago; Uniforms--Trinidad and Tobago; Military uniforms--Trinidad and Tobago; Armored troops—Uniforms; Blackboards; Signs and signboards--Trinidad and Tobago